Power for the planet - Flounders, Anne (Red Chair Press, 2014)
Scientists tell us that some of the fuels that keep our homes and businesses running, power our transportation, and keep us safe are hurting the Earth. Learn why energy companies are working to come up with cleaner ways to supply oil and gas, how fuels in the future will be safer for Earth, and what you can do now to use energy wisely. Includes step-by-step ideas for taking action, different points of view, an up-close look at relevant careers, and more.